1977
DOI: 10.1177/074171367702700201
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adult Student Participation in Program Planning On Achievement, Retention and Attitude

Abstract: The purpose of this study was to investigate the influence of adult student participation in program planning on student achievement, retention, and attitude. Participants in two in-service groups at a North Carolina hospital were assigned to two experimental classes. One class participated in planning its educational program; the second completed a course identical to the one planned by the first, but was given no opportunity to participate in planning the course objectives and design.The results permitted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…ing elements: (1) establishing a climate conducive to learning; (2) creating a mechanism for mutual planning; (3) diagnosing the needs for learning; (4) formulating program objectives that will satisfy these needs; (5) designing a pattern of learning experiences; (6) conducting these learning experiences with suitable techniques and materials; and (7) evaluating the learning outcomes and rediagnosing learning needs. In addition to giving freedom to express opinions, ask questions, and do things in a new way, therefore, some instructors, according to Knowles, may use teaching behaviors that involve students in the planning, operation, and assessment of an educational program.…”
mentioning
confidence: 99%
“…ing elements: (1) establishing a climate conducive to learning; (2) creating a mechanism for mutual planning; (3) diagnosing the needs for learning; (4) formulating program objectives that will satisfy these needs; (5) designing a pattern of learning experiences; (6) conducting these learning experiences with suitable techniques and materials; and (7) evaluating the learning outcomes and rediagnosing learning needs. In addition to giving freedom to express opinions, ask questions, and do things in a new way, therefore, some instructors, according to Knowles, may use teaching behaviors that involve students in the planning, operation, and assessment of an educational program.…”
mentioning
confidence: 99%
“…This study did not show a relationship between student planning and achievement, as measured by a multiple-choice achievement test. Cole and Glass (1977), in a study with eighteen in-service adult students at a North Carolina hospital, found that student participation in course planning positively affected student achievement, although not their retention of information. As in the McLoughlin study, participation in program planning was found to positively influence adult students' attitudes regarding the course.…”
mentioning
confidence: 99%
“…As with other groups of learners. Cole and Glass (1977) found that achievement scores of adult learners were higher and that more positive attitudes by adult learners toward education resulted if the atmosphere was perceived by learners as interactive.…”
Section: Adult Participationmentioning
confidence: 97%
“…Other researchers were able to determine that various relationships do exist between the instructor and other variables. Beder & Darkenwald (1982), Cole and Glass (1977), Holmes (1982), Menlo and Miller (1976), Yee-Lay and Wong (1974) all concluded that certain interpersonal behaviors of the instructor such as expressing a desire to cooperate, or displaying a willingness to interact, resulted in increased attendance. Increased learner involvement, and a more interactive atmosphere.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation